2004
DOI: 10.1210/en.2004-0015
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Glucagon-Like Peptides Regulate Cell Proliferation and Apoptosis in the Pancreas, Gut, and Central Nervous System

Abstract: Gut peptides exert diverse effects regulating satiety, gastrointestinal motility and acid secretion, epithelial integrity, and both nutrient absorption and disposal. These actions are initiated by activation of specific G protein-coupled receptors and may be mediated by direct or indirect effects on target cells. More recent evidence demonstrates that gut peptides, exemplified by glucagon-like peptides-1 and 2 (GLP-1 and GLP-2), directly regulate signaling pathways coupled to cell proliferation and apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
345
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 495 publications
(356 citation statements)
references
References 109 publications
7
345
0
4
Order By: Relevance
“…It is generally believed that islet precursor cells exist in the pancreatic ducts [31]. GLP-1 has been shown to induce the production of PDX1 in ducts and the differentiation of duct cells toward insulin-producing cells [32]. In GLP-1-treated NOD mice, we found that the number of newly formed beta cells originating from pancreatic ducts was increased.…”
Section: Discussionmentioning
confidence: 65%
“…It is generally believed that islet precursor cells exist in the pancreatic ducts [31]. GLP-1 has been shown to induce the production of PDX1 in ducts and the differentiation of duct cells toward insulin-producing cells [32]. In GLP-1-treated NOD mice, we found that the number of newly formed beta cells originating from pancreatic ducts was increased.…”
Section: Discussionmentioning
confidence: 65%
“…In animals with grafts of 75 islets, the body weights of the exendin-4-treated animals were similar to those of PBS-treated animals, although the exendin-4 mice tended to recover the weight loss after nephrectomy more quickly. It has previously been reported that exendin-4 slows gastric emptying, and therefore animals can lose weight [5]. However, it may be possible that the improvement in glucose homeostasis itself leads to a weight gain despite the effects on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…Exendin-4 is an agonist of the glucagon like peptide-1 (GLP-1) receptor with a longer half-life than GLP-1 [5]. This peptide has previously been shown to increase beta cell replication and islet neogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the normal number of beta cells is maintained in a balance between apoptosis and proliferation, this observation is of considerable interest, and raises the possibility that GLP-1 could be useful in conditions in which beta cell apoptosis is increased. The complicated mechanisms whereby GLP-1 may exert these effects on beta cells were reviewed recently [96].…”
Section: Protective Effects Of Glp-1mentioning
confidence: 99%